Effect of tool holder geometry and cutting condition when milling nickel-based alloy 242 - Habeeb H.H.; Abou-El-Hossein K.A.; Mohammad B.; Kadirgama K. (2023)
This paper presents an experimental study about the influence of tool holder's geometry and cutting parameters on tool wear and tool life when milling nickel based alloy 242 with carbide inserts of different coatings. In this study, TiAlN, TiCN/TiN, TiAlN/TiN and TiCN/Al2O3 coated carbide inserts were employed. Aerospace and power industries are the most common users of nickel-based alloys because of their good strength to weight ratio and superior corrosion resistance. However machining of these alloys is a very difficult task due to their poor machineability. In this study, it was found that during machining of nickel-based alloys 242 with a tool holder providing geometry of 90 shoulder cutting, the tool wear rate progressed more rapidly compared to the 70-tool holder. Generally, the cutting inserts were rejected mainly due to intensive wear on the flank face and the surrounding area. High abrasion wear was observed on the flank face of the cutting tools. It was observed that the TiCN/Al2O3 coating demonstrated more susceptibility to edge chipping compared to the other types of coating. 2007 Elsevier B.V. All rights reserved.